Photographic Archives and the Anthropology of Communism in Albania - de Rapper Gilles (Comparative Southeast European Studies, 2022)
The communist period in Albania was a time of intense photographic production. Much more than in previous periods, photography was perceived by those in power as an indispensable tool while at the same time becoming accessible to almost the entire population. Many photographs from the time survived the end of the communist regime and can now be used to study the history and memory of that period. To be of historical value, however, the diversity of photographic genres and practices, as well as the history of the constitution of photographic archives demands consideration of the context of the production and circulation of photographs, and that is a primary objective of this article. The author shows how he conducted an ethnography of photography based on presentation of the current state of public and private collections, and how such investigation constitutes a contribution to the anthropology of communism in Albania.